Laju Dekomposisi Serasah Daun Mangrove Bruguiera gymnorrhiza dan Sonneratia alba di Kawasan Hutan Mangrove Pulau Penyu, Tanjung Benoa, Bali - Artha C. Rosevina Anak Ampun; I Wayan Gede Astawa Karang; Yulianto Suteja (Journal of Marine and Aquatic Sciences, 2020)
Mangroves are plants that play an important role in maintaining the fertility of mangrove ecosystems by contributing organic material derived from leaf litter. The rate decomposition of leaf litter is a destruction process by dead organisms into smaller particles. The decomposition process of mangrove leaf is affected by lignin and wax in nitrogen supply, environmental conditions, abundance of organisms, and air temperature. This research aims to determine the decomposition rate of leaf litter and percentage decomposition of Bruguiera gymnorrhiza and Sonneratia alba in mangrove forest area in Penyu Island, Tanjung Benoa, Bali. This research was conducted from February to April 2017. The method in this research used litter trap method. The location of the stations was based on the distance of the mangrove trees to the sea. Litter traps were placed on the six (6) stations. During the 60 days of decomposition process, Sonneratia alba leaf was decomposed faster than Bruguiera gymnorrhiza. The highest decomposition rate of Sonneratia alba leaf litter found at station 1 (1.7 g/day) with 99.9% decomposed, and the lowest at station 2 (1.38 g/day) with 99.64% decomposed. The highest decomposition rate of Bruguiera gymnorrhiza leaf litter found at station 1 (1.52 g/day) with 98.88% decomposed, and the lowest at station 2 (0.99 g/day) with 84.66% decomposed.